A novel current control technique for photo voltaic integrated single phase shunt active power filter - Rameshkumar, K. (International Journal of Renewable Energy Research, 2017)
In this paper a Model Predictive Current Control (MPCC) of single phase Photo Voltaic (PV) integrated Shunt Active Power Filter (SAPF) is proposed. A PV integrated single phase Voltage Source Inverter (VSI) is used to generate a part of the real power and compensate harmonics, reactive power of a Non-Linear Load (NLL). In this paper, a DC link voltage regulation based PI control algorithm is adopted for determining the reference current at the filter side. The performance of SAPF with PV and associated control methods like switch on response and change of nonlinear load were carried out. Also, the performance of the controller has been examined with variation in irradiance, filter inductance value and variation in controller sampling time through a simulation in MATLAB software.